Utilization of organic domestic waste as liquid organic fertilizer at PCM Colomadu - Suparti Suparti; Aminah Asngad; Lina Agustina; Rina Astuti; Ambarwati Ambarwati; Dwi Setyo Astuti; Erma Musbita Tyastuti; Siti Kartika Sari; Ria Anisa Fani; Muhammad Fauzi Nurromadhon; Firstnanda Ivanka Putri; Shalsa Shabilla Isna Putri; Siti Nur Syarifah; Nila Permatasari; Warsiti Warsiti (Community Empowerment, 2022)
The amount of organic household waste creates new problems in the environment, so there needs to be a solution to reduce waste. One of them is by making liquid organic fertilizer. The purpose of this community service is to provide training on the manufacture of liquid organic fertilizer from household waste. The method in this community service activity is to provide training on making POC from organic waste, conducting NPK POC tests, training and assistance in making POC product packaging at PCM Colomadu (Women Farmers Group (KWT) Berkah Tani 2). The result of this community service activity is that the KWT Berkah Tani 2 gains experience in making POCs so that they can help reduce organic waste in the Colomadu area.